Church, Lies, and Polling Data - Walsh, Andrew 1969- (1998)
Americans may be lying to poll-takers about how often they attend worship, but many journalists and social scientists are wedded to the old pieties
Keywords: Religious surveys; Public opinion polls; Church Attendance; Church statistics; United States